Analisis Kinerja Biaya dan Waktu dengan Metode Earned Value pada Proyek Transportasi Bandar Udara - Isfan Dina; Budi Susetyo; Agus Suroso (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
The Ministry of Transportation plans to build 16 national strategic airports by 2021. The airports to be built are spread from Sumatra to Papua with a total budget of IDR 1.6 trillion. Projects that are complex and dynamic in their implementation have caused many projects not to go according to plan. Both in terms of time, cost and labor. For this reason, it is necessary to have a consistent and integrated control mechanism for project performance. Earned Value Management (EVM) is one of the appropriate project management techniques used to compare actual work performance against project plans. Outline of project control can identify such as: Time and Schedule ; Is the time used to be longer or faster than the original plan? then, Budget and Costs; Does the budget used exceed the initial budget that has been determined or not, and Performance; Does performance lead to real productivity at the time of reporting? The results of the study explain that in weeks 9 to 12 the SPI value < 1 which indicates that the project is experiencing delays, and starts on schedule in week 13 and accelerates in week 14 while in weeks 15 and 16 it experiences delays again because the value SPI < 1 and back on schedule in week 17. Meanwhile, based on the value of the Cost Performance Index (CPI) only in week 11, the value of CPI < 1 shows that the actual costs incurred are greater than the completion of the volume of work, resulting in cost overruns). and the amount of money needed to complete the rest of the work is Rp. 1,519,229,597.61 with a total project cost of Rp. 6,779,248,539.11 and the estimated time for completion of this project is 22 weeks.